Epicardial Fat Tissue Thickness Correlates with Endothelial Dysfunction and Other Cardiovascular Risk Factors in Patients with Metabolic Syndrome - YAVUZ, DİLEK; ÜSTAY, ÖZLEM (MARY ANN LIEBERT, INC, 2010)
Background: Epicardial adipose tissue has shown to be related to cardiovascular risk. The aim of this study is to investigate the relationship between epicardial adiposity and endothelial function in metabolic syndrome. Methods: Fifty patients with metabolic syndrome were recruited. Anthropometric measurements, fasting blood glucose, insulin, lipid profile, high-sensitivity C-reactive protein (hsCRP), fibrinogen, apolipoprotein A (Apo A), Apo B1, and lipoprotein (a) [Lp(a)] were determined. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. Epicardial fat thickness was measured via two-dimensional M-mode echocardiography. Endothelial function was assessed as flow-mediated dilatation at the brachial artery. Results: Epicardial fat tissue thickness was shown to be correlated negatively with FMD and positively with age, diastolic blood pressure, hsCRP, fibrinogen, HOMA-IR, and lipid parameters. Multiple regression analysis showed epicardial fat tissue thickness to be an independent factor influencing the endothelial function. Conclusions: Epicardial fat tissue may be a useful parameter in the assessment of patients with metabolic syndrome.
Keywords: ADIPOSE-TISSUE; ADIPONECTIN EXPRESSION; VISCERAL ADIPOSITY; DISEASE; OBESITY